2017
DOI: 10.1038/s41598-017-11484-7
|View full text |Cite
|
Sign up to set email alerts
|

Lateral movements of a massive tail influence gecko locomotion: an integrative study comparing tail restriction and autotomy

Abstract: Tails are an intricate component of the locomotor system for many vertebrates. Leopard geckos (Eublepharis macularius) possess a large tail that is laterally undulated during steady locomotion. However, the tail is readily shed via autotomy, resulting in the loss of tail function, loss in body mass, and a cranial shift in the center of mass. To elucidate the function of tail undulations, we investigated changes in limb kinematics after manipulating the tail artificially by restricting tail undulations and natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 59 publications
(70 reference statements)
2
26
0
Order By: Relevance
“…Recent research has built upon these findings by investigating the kinematic and morphological mechanisms that decrease locomotor performance after autotomy. For instance, Jagnandan & Higham () experimentally demonstrated that changes in the locomotion of lizards after tail loss were due to the absence of lateral undulations of the tail, rather than the loss of body mass per se or the anterior shift in the centre of mass. Additionally, in Anolis carolinensis , tail autotomy affected their in‐air stability while jumping (Gillis, Bonvini, & Irschick, ).…”
Section: Variation In the Costs And Benefits Of Autotomymentioning
confidence: 99%
“…Recent research has built upon these findings by investigating the kinematic and morphological mechanisms that decrease locomotor performance after autotomy. For instance, Jagnandan & Higham () experimentally demonstrated that changes in the locomotion of lizards after tail loss were due to the absence of lateral undulations of the tail, rather than the loss of body mass per se or the anterior shift in the centre of mass. Additionally, in Anolis carolinensis , tail autotomy affected their in‐air stability while jumping (Gillis, Bonvini, & Irschick, ).…”
Section: Variation In the Costs And Benefits Of Autotomymentioning
confidence: 99%
“…Eublepharis macularius stores large quantities of fat in its tail (Cheek, 2005;Lynn et al, 2013;Jagnandan, Russell & Higham, 2014;Russell, Lynn, Powell, & Cottle, 2015), a load which must be compensated for in locomotion. The tail is held off the ground as the lizard walks at a normal pace, the standing wave produced by locomotory undulations of the trunk being transmitted as a travelling wave producing undulations in the tail (Jagnandan & Higham, 2017). The tail is autotomic (Cheek, 2005;Jagnandan et al 2014;Lynn et al, 2013;Russell et al, 2015), and loss of the entire tail results in the instantaneous loss of a considerable amount of weight (20-23% of total body mass in juveniles [Lynn et al, 2013]; 25% of total body mass in adults [Jagnandan et al, 2014]), and to the sudden absence of an appendage that plays a significant locomotory role (Gillis & Higham, 2016;Jagnandan & Higham, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The tail is held off the ground as the lizard walks at a normal pace, the standing wave produced by locomotory undulations of the trunk being transmitted as a travelling wave producing undulations in the tail (Jagnandan & Higham, 2017). The tail is autotomic (Cheek, 2005;Jagnandan et al 2014;Lynn et al, 2013;Russell et al, 2015), and loss of the entire tail results in the instantaneous loss of a considerable amount of weight (20-23% of total body mass in juveniles [Lynn et al, 2013]; 25% of total body mass in adults [Jagnandan et al, 2014]), and to the sudden absence of an appendage that plays a significant locomotory role (Gillis & Higham, 2016;Jagnandan & Higham, 2017). E. macularius adopts a more sprawling locomotory posture after tail loss, principally through adjustment of the angles adopted by the segments of the hindlimb, and pelvic rotation is reduced (Jagnandan & Higham, 2017;Jagnandan et al, 2014), but walking speed is unaffected (Jagnandan & Higham, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, animals living in aquatic environments, such as fish or crocodiles, use their tail mainly as a propelling device [2,3]. Land vertebrates also benefit of the tail for locomotive purposes, either as an additional leg for kangaroos, facilitating walking mechanics in lizards, or serving as a counterbalance to help animals like cats or mice move through narrow or unstable surfaces [4][5][6][7]. An interesting variation upon this function was the evolution of prehensile tails, which allow grasping and holding to objects [8,9].…”
Section: Introductionmentioning
confidence: 99%